SOCIAL COMMUNICATION SKILLS OF EMPLOYEES AND ITS IMPACT ON THE TOURIST BEHAVIOR: AN EXPLORATORY STUDY OF THE OPINIONS OF A SAMPLE OF VISITORS TO THE BAGHDADI MUSEUM - Maryam Hassan Obaid Al-Dulaimi; A.M. Dr. Alaa Karim Mutlaq (Scholar Express Journals, 2023)
The current study contributed to highlighting social communication(SC) skills of employees and its impact on the behavior of tourists (PT), and extent to which the nature of that relationship is reflected in field reality to promote tourist destinations , their success , Study stemmed from a real problem at tourist attractions suffer from, especially in particular, the sample of the current study, the Baghdadi museum, as a result of lack of interaction between visitors to Baghdadi Museum and specialized workers in the tourism sector, through exposure of workers to barriers that lead to the failure to achieve effective communication, including language problems psychological barriers, Misunderstanding, cultural differences , other things that a worker in the tourism sector must master these skills in a verbal , non-verbal form with electronic to ensure effective communication and return of the tourist to visit tourist destination, and the girls have importance of studying in general on profession of workers in the tourism sector, This is proved by the reflection of those impressions in the formation of the tourist's mental image, as it is considered an acceptable approach as an indicator of sustainable swimming, as it relied on resolution as the main tool for data collection and relied on the five-point Likert scale , Sample size was (194), The study reached the most important conclusions and recommendations, most important of which is that verbal fluency, proper speech , speaking spontaneously is an important factor in forming the mental image of a tourist with a positive or negative view of a particular topic, idea or place, The respondents stressed that there are significant differences between the Baghdadi Museum and international museums in terms of organization and services, and one of most important recommendations included in study need for employees at the Baghdadi museum to enjoy etiquette while dealing with other visitors, which begins by instinct and acquired by training
Keywords: Social Media; skill; skills of workers